Effects of different nitrogen application rates and picking batches on the nutritional components of Lycium barbarum L. fruits - Liang, Xiaojie; An, Wei; Li, Yuekun; Qin, Xiaoya; Zhao, Jianhua; Su, Shuchai (Frontiers in Plant Science, 2024)
Lycium barbarum L., commonly known as wolfberry, is not only a traditional Chinese medicine but also a highly nutritious food. Its main nutrients include L. barbarum polysaccharide, flavonoid polyphenols, carotenoids, alkaloids, and other compounds, demonstrating its wide application value. This study investigated the effects of nitrogen application on the accumulation of the main nutrients and metabolites in wolfberry fruits under three different nitrogen application rates, namely, N1 (20% nitrogen (N) reduction, 540 kg·ha–2), N2 (medium N, 675 kg·ha–2), and N3 (20% nitrogen increase, 810 kg·ha–2,which is a local conventional nitrogen application amount. ). Additionally, due to continuous branching, blossoming, and fruiting of wolfberry plants during the annual growth period, this research also explored the variation in nutritional composition among different harvesting batches. The contents of total sugar and polysaccharide in wolfberry fruit were determined by Fehling reagent method and phenol-sulfuric acid method, respectively;The content of betaine in fruit was determined by high-performance liquid chromatography,and the flavonoids and carotene in the wolfberry fruits were determined by spectrophotometry.Analysis of data over three consecutive years revealed that as nitrogen application increased, the total sugar content in wolfberry fruits initially decreased and then increased. The levels of L. barbarum polysaccharides, total flavonoids, and total carotenoids initially increased and then decreased, while the betaine content consistently increased. Different picking batches significantly impacted the nutrient content of wolfberry fruits. Generally, the first batch of summer wolfberry fruits had greater amounts of total sugar and flavonoids, whereas other nutrients peaked in the third batch. By employing a broadly targeted metabolomics approach, 926 different metabolites were identified. The top 20 differentially abundant metabolites were selected for heatmap generation, revealing that the contents of L-citrulline, 2-methylglutaric acid, and adipic acid increased proportionally to the nitrogen gradient. Conversely, the dibutyl phthalate and 2, 4-dihydroxyquinoline contents significantly decreased under high-nitrogen conditions. The remaining 15 differentially abundant metabolites,kaempferol-3-O-sophorosid-7-O-rhamnoside, trigonelline, and isorhamnosid-3-O-sophoroside, initially increased and then decreased with increasing nitrogen levels. Isofraxidin, a common differentially abundant metabolite across all treatments, is a coumarin that may serve as a potential biomarker for wolfberry fruit response to nitrogen.